THU0577 Do raynaud phenomenon negative juvenile systemic scleroderma patients have a different pattern of organ involvement as raynaud phenomenon positive patients?. (12th June 2018) - Foeldvari, I.; Klotsche, J.; Kasapcopur, O.; Adrovic, A.; Torok, K.; Stanevicha, V.; Terreri, M.T.; Alexeeva, E.; Katsikas, M.; Smith, V.; Sztajnbok, F.; Avcin, T.; et al.
Abstract : Background: Juvenile systemic scleroderma (jSSc) is an orphan disease, with an estimated prevalence of 3 per 1000 000 children. Most jSSc patients primarily present with Raynaud phenomenon (RP). We investigated in our patient of the juvenile scleroderma inception cohort, how fare patients with (RP+) and without (RP-) RP differed in their clinical presentation at enrolment. Methods: The jSSc is a prospective cohort of jSSc patients. Patients were enrolled who were diagnosed with jSSc, had a jSSc onset age under 16 years and were younger as age of 18 years at the time of inclusion. The patients are prospectively assessed every 6 months according to a standardised protocol. We reviewed the organ involvement pattern of our patients currently followed in the cohort. Results: 100 patients are currently followed in the cohort and 89 (89%) of them had RP. The female/male ratio was lower in the RP +group, 3.7:1 compared to 4.5:1(p=0.808). Diffuse subtype was more common in the RP +group, 72% compared to 63%. Mean age of onset of first non- Raynaud symptomatic was 10.4 years in both groups. Mean disease duration was slightly higher in the RP +group, 3.4 compared to 2.2 years. ANA positivity was higher in the RP +group, 88% compared to 70% (p=0.48). Anti-Scl70 was 34% in the RP +and 20% in the RP-group (p=0.34). Interestingly 7% of RP +but none of the RP +were anti-centromere positive. The mean modified skin score was lower in RP +group (mean of 14.8 compared to 17.0). There were significantly more nailfold capillary changes (70% compared to 18%, p=0.001) and a higher rate of history of ulceration in the RP +group (49% compared to 20%, p=0.083). Decreased DLCO and FVC <80% was higher in the RP-negative group with 45%/50% compared to 37.5%/31% respectively. Pulmonary hypertension occurred in 7% in the RP +group and there was no case in the RP- group (p=0.335). RP- group had a higher rate of urinary sediment changes 18% compared to 4.5% in the RP +group (p=0.07). No renal crisis or hypertension was reported in neither groups. Gastrointestinal involvement was similar between the two groups with around 35%. Occurrence of swollen joints was similar in both groups as the frequency of muscle weakness with around 20%. The tendon friction rub occurred around 10% in both groups. In the patient related outcomes, there was only a difference in rating of Raynauds activity. Conclusions: The RP– group differed from RP +group in the clinical presentation at enrolment. The absence of Raynaud phenomenon was associated with a decreased rate of history of ulceration, no occurrence of pulmonary hypertension. Interestingly higher rate of urinary sedimentary changes and no anticentromere positivity was observed in RP- patients. Disclosure of Interest: None declared